A PRAGMATIC ANALYSIS OF SLOGAN USED IN MOBILE PHONE BRAND - EDDRY Y, PHENGKY (2011)
This research is aimed at describing the linguistic forms and meanings of each slogan used in mobile phone brands. The data are slogans that are in the form of phrase, clause, and sentence taken from internet, TV advertisement and magazine. In collecting the data, the writer uses documentation method by selecting and writing the slogan which is found in internet, TV advertisement and magazine. To describe the linguistic forms the writer refers to linguistic form theory. In determine the meaning of slogan, the writer uses implicature theory. Having analyzed the data, the writer finds that the linguistic forms of slogans which are used in mobile phone brands. There are fifteen forms of noun phrase and two verb phrase. There is only one clause in the form of noun clause. Then, there are three imperative sentences. And also the meaning of slogans that are to inform consists of eleven data, to persuade consists of thirteen data and to assert consists of six data.